2010
DOI: 10.1016/j.jvs.2009.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of open versus endovascular repair for ruptured descending thoracic aortic aneurysm

Abstract: Endovascular repair of rDTAA is associated with a significantly lower 30-day mortality rate compared with open surgical repair. TEVAR was associated with a considerable number of aneurysm-related deaths during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
129
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(143 citation statements)
references
References 49 publications
7
129
1
6
Order By: Relevance
“…In a recent meta-analysis comparing endovascular repair and OR for ruptured DTAA, the 30 day mortality was 19% and 33%, respectively. 126 Lower rates of myocardial infarction (3.5%), stroke (4.1%), and paraplegia (3.1%) were noted The need for LSA revascularisation in challenging proximal aortic neck anatomy is controversial, especially in acute cases. LSA coverage, to achieve a satisfactory proximal seal during TEVAR for ruptured DTAA, is reported in up to 38% of cases.…”
Section: Iib B 104mentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent meta-analysis comparing endovascular repair and OR for ruptured DTAA, the 30 day mortality was 19% and 33%, respectively. 126 Lower rates of myocardial infarction (3.5%), stroke (4.1%), and paraplegia (3.1%) were noted The need for LSA revascularisation in challenging proximal aortic neck anatomy is controversial, especially in acute cases. LSA coverage, to achieve a satisfactory proximal seal during TEVAR for ruptured DTAA, is reported in up to 38% of cases.…”
Section: Iib B 104mentioning
confidence: 97%
“…Generally, DTAA rupture is contained by periaortic structures (pleura, pericardium) or intrathoracic organs (oesophagus, lungs, heart). 126 Major complications of myocardial infarction, stroke, and paraplegia have been reported to occur in 11.1%, 10.2%, and 5.5%, respectively. Another recent multicenter, retrospective review of 69 patients with ruptured DTAA published by the same authors demonstrated a composite outcome of death, stroke, or permanent paraplegia in 36.2%.…”
Section: Iib B 104mentioning
confidence: 99%
“…TEVAR has emerged as the treatment modality of choice in patients presenting acutely with aortic catastrophes such as traumatic aortic transection, complicated type B dissection and ruptured aneurysms [22][23][24]. Emergency open repair of thoracic aortic disease is universally associated with high short-term mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The desire to see more patients survive to hospital discharge will mean that few surgeons will choose open repair over TEVAR in the emergency setting. This will be at the expense of increased re-interventions and possibly equivalent longterm outcomes as well as the potential for incomplete exclusion of the pathology, especially for ruptured aneurysmal disease [24]. The situations where more equipoise exists include elective repair of asymptomatic thoracic aortic aneurysm where TEVAR may not be superior to open repair and has an unproven durability.…”
Section: Resultsmentioning
confidence: 99%
“…For patients who present with ruptured descending thoracic aneurysms, the most comprehensive data have been collated by Jonker et al 11) , who recently published a metaanalysis comparing open versus endovascular techniques for this subgroup of patients. Extracting data from 24 studies involving 143 patients treated by TEVAR and 81 patients with open surgery, the authors found a significantly lower 30-day mortality rate in the TEVAR group (OR, 2.15; p = 0.016).…”
Section: Ruptured Descending Thoracic Aneurysmsmentioning
confidence: 99%